E - mpathy – Powerfull AR learning tool to improve Call Center Representative Soft Skills (2024)
E - mpathy is a solution based on virtual reality technology aimed at improving the soft skills of customer service agents through immersive, kinesthetic learning under the 'learning by doing' model. With this solution, agents easily acquire communication skills that assist them in their day - to - day tasks and ultimately contribute to the organization achieving better metrics in customer satisfaction, average interaction time, and staff retention.